A novel sulfonated aromatic polyimide synthesis and characterization: Energy calculations, QTAIM simulation study of the hydrated structure of one unit. (10th April 2022) - Yildiko, Umit; Tanriverdi, Aslihan Aycan
Abstract: A new type of sulfonated polyimide was synthesized from a one‐step polycondensation reaction with perylene‐3, 4, 9, 10‐tetracarboxylic dianhydride and 4, 4′‐diamino‐2, 2′‐stilbenedisulfonic. Pure characterization of sulfonated polyimide (SPI) was performed by Fourier transform infrared spectroscopy, proton nuclear magnetic resonance, thermogravimetric analysis, differential thermal gravimetric analysis, ultraviolet–visible spectroscopy, and solubility tests. Moreover, the SPI film was prepared by a thermal imidization step heating procedure. Furthermore, quantum chemical calculations of the synthesized SPI were investigated with density functional theory (DFT) and time‐dependent density functional theory. By calculating the frontiers molecular orbital energies of the obtained polyimide, the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO), and the energy gap (Δ) values were found for the one structural unit and three structural units of SPI, respectively. Also, QTAIM was carried out based on the AIMAll program. With the increase in water molecules, the average electronic energy density (HBCP ) value decreased according to the results of QTAIM. The SPI can be used as a potential membrane in fuel cells. Abstract : This account highlights is the synthesis of a new type of sulfonated polyimide (SPI) from a one‐step polycondensation reaction with Perylene‐3, 4, 9, 10‐tetracarboxylic dianhydride and 4, 4′‐diamino‐2, 2′‐stilbenedisulfonic acid. It is also emphasized that the SPI film is prepared by a thermal imidization step heating procedure. Pure characterizations and solubility tests of sulfonated polyimide are presented. In addition, quantum chemical calculations of the synthesized SPI were investigated with DFT, TD‐DFT and QTAIM.